KONSEP UANG DALAM PERSPEKTIF EKONOMI ISLAM: ANALISIS FILOSOFIS DAN NORMATIF - Shely Nurlela; Annita Firda; Doli Abdul Hamid Manullang; Muhammad Arfan Harahap (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
This study aims to investigate the meaning of money from an Islamic economic perspective in a philosophical and normative manner. In traditional economics, money is considered a medium of exchange, a store of wealth, and a morally neutral unit of measurement. However, from an Islamic economic perspective, money plays more than just an economic role, but also embodies ethical and moral values ​​based on the principles of monotheism, justice, and general welfare. Philosophically, money is seen as a trust that should be used for productive activities and should not be traded as a speculative commodity. From a normative perspective, the concept of money is governed by sharia rules that prohibit usury, gharar, and maisir, and prioritize the circulation of wealth in the real sector. Therefore, in Islamic economics, money acts as a tool to achieve prosperity and social justice, not to accumulate wealth. This study is expected to deepen the understanding that the monetary system in Islam places money as a means of distributing value and welfare in line with the maqashid of sharia.